Absorption of Bupivacaine after Administration of a Lozenge as Topical Treatment for Pain from Oral Mucositis. Issue 1 (26th September 2016) - Mogensen, Stine; Sverrisdóttir, Eva; Sveinsdóttir, Kolbrún; Treldal, Charlotte; Jensen, Kenneth; Jensen, Anders Bonde; Kristensen, Claus Andrup; Jacobsen, Jette; Kreilgaard, Mads; Petersen, Janne; Andersen, Ove
Abstract: The aim was to investigate systemic exposure after administration of a novel bupivacaine lozenge in healthy individuals with normal mucosa and in head and neck cancer (HNC) patients with oral mucositis. A lozenge containing 5, 10, 25 and 50 mg bupivacaine, respectively, was administered as single dose to 10 healthy individuals, and a lozenge containing 25 mg bupivacaine was administered as single dose to 10 HNC patients with oral mucositis and as multiple doses to five patients with HNC. Blood samples were collected for 6 hr from the healthy individuals and 3 hr from the patients with HNC, respectively, after administration. The plasma concentration–time profiles of bupivacaine were fitted to pharmacokinetic models using nonlinear mixed‐effects modelling, evaluating demographics and health status as covariates. The population pharmacokinetics (PK) of bupivacaine lozenge was best described by a two‐compartment distribution model with absorption transit compartments. All the observed plasma concentrations were well below the bupivacaine concentrations (2000–2250 ng/ml) which have caused toxic symptoms. The PK model suggested that relative bioavailability was two times higher in HNC patients with oral mucositis grade 1–2 and three times higher in HNC patients with oral mucositis grade 3–4 than in the healthy individuals. Simulations showed that the plasma concentrations would be below the toxic limit after repeated dosing every second hour with 25 mg bupivacaine for five days. The 25‐mg bupivacaine lozenges were safe without systemic toxic levels of bupivacaine or risk of side effects. Based on PK simulations of repeated doses of 25 mg every two hours for 16 hr a day, the lozenges can be administered with minimum risk of exceeding the toxic limit.